(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines extralinguistic factors within cross-cultural communication. Special attention is given to gestures, silence, politeness, and facial expressions. The study analyzes their pragmatic and linguocultural meanings. Different cultures interpret nonverbal communication differently. Misunderstandings often appear during intercultural interaction. The article discusses communicative behavior in various social situations. Real communicative examples are analyzed pragmatically. The research highlights cultural influence on interpersonal communication. The findings reveal the importance of extralinguistic factors in effective interaction.